2023
DOI: 10.1007/s11695-023-06572-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bariatric Surgery on Erectile Dysfunction—a Systematic Review and Meta-Analysis

Abstract: Introduction Obesity is associated with a higher prevalence of various comorbidities including erectile dysfunction (ED). Bariatric surgery leads to weight loss and remission of weight-related diseases. The exact influence of bariatric treatment on ED is yet to be established; however, the number of papers on the subject is growing. Methodology A systematic review with meta-analysis comparing erectile dysfunction before and after surgery was conducted acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent systematic review involving 14 studies and 508 patients clearly showed remarkable benefits of improvement of T levels and erectile function in patients following weight loss after bariatric surgery[ 40 ]. Trials evaluating the effect of MBS on semen morphology are highly variable and inconsistent, with small prospective studies reporting a decrease in the percentage of sperm with normal morphology.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…A recent systematic review involving 14 studies and 508 patients clearly showed remarkable benefits of improvement of T levels and erectile function in patients following weight loss after bariatric surgery[ 40 ]. Trials evaluating the effect of MBS on semen morphology are highly variable and inconsistent, with small prospective studies reporting a decrease in the percentage of sperm with normal morphology.…”
Section: Bariatric Surgerymentioning
confidence: 99%